Analysis of character value implementations in high school mathematics learning - Gelcy Vania Auliani; Intan Amalia; Nabilah Putri; Sya’rani Naila Firindi; Nyimas Aisyah; Elsa Susanti (Universitas Sriwijaya, 2025)
Character education plays an important role in shaping individuals who not only excel academically but also possess strong morals and high social values. In the context of mathematics learning, character values not only help students understand numerical concepts but also instill discipline, hard work, and perseverance. This study aims to analyze the implementation of character values in mathematics learning and the role of teachers in developing them. The subjects of the study were 100 high school students from public schools in Palembang. Data were collected through questionnaires and interviews and analyzed using descriptive methods. The results showed that the values of discipline, hard work, and religiosity were dominant, while creativity and communication remained weak. Therefore, efforts are needed to develop these values, particularly creativity and communication, through improved teacher professionalism, interactive learning, integration of real-world contexts, and addressing students' psychological barriers.